Pemanfaatan Batu Sungai Mappak Kabupaten Tana Toraja Dalam Campuran Laston Lapisan Antara - Barrung, Remsi; Nurdin, Abd. Rahim; Mallawangeng, Tamrin (Jurnal Penelitian Teknik Sipil Konsolidasi, 2024)
This research aims to find out how the aggregate characteristics of the Mappak River in Tana Toraja Regency can be used as a pavement material for asphalt mixtures. The method used is the conventional marshall method to obtain the properties of the mixture and marshall immersion to obtain residual marshall stability from the optimum asphalt content mixture. The results of the study indicated that the aggregate characteristics of the Mappak River stone in Tana Toraja Regency with an aggregate wear value of 21.6% met the specifications as a road pavement layer material for Mixed Laston Intermediate Layers with Optimum Asphalt Content of 6.20%, with the mixed properties of Laston Intermediate Layers, namely Density, Stability, flow, VIM, VMA, VFB and Marshall Quentient have met the Specifications of Bina Marga 2018. Through Marshall Immersion testing the Laston Intermediate Layers mixture with Optimum Asphalt Content of 6.20% obtained Remaining Marshall Stability of 95.07%, which means that it meets the Specifications Bina Marga 2018, namely at least 90%..